Shade Effect on Growth and Quality of Cempaka Wasian Seedling (Magnolia tsiampaca (Miq.) Dandy) in Nursery - Arif Irawan; Hanif Nurul Hidayah (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2017)
Cempaka wasian (Magnolia tsiampaca (Miq) Dandy )) is one tree species with high economic value. Cempaka wasian development in the form of community forests in the province of North Sulawesi needs to be supported by the availability of quality seeds. Generally, plant has different effect towards light it received. This study aimed to determine the effect of shade intensity on the growth of seedlings in the nursery. The experimental design used in this research is completely randomized design. The treatments were tested among other shade with a density of 25 % (± 37,350 lux light intensity), the shade with a density of 50 % (± 19,100 lux light intensity) and shade with a density of 75 % (± 8,018 lux light intensity). The results showed that treatment with 50% shade density (± 19,100 lux light intensity) gives the best effect on the growth and quality of seedlings in the nursery.Keywords : cempaka wasian , shade , seeds